Automation Of Trash Can Collection Using Line Follower Based On Wireless Control - Hidayatus Sibyan; M. Fuat Asnawi; Dwitya Ilham Kurniadi (Nacreva Publisher, 2022)
Every school must have a cleaning staff whose job is to care for and maintain the cleanliness of the school building. At SMKN 2 Bawang, the building is spacious and separated between buildings, so collecting waste requires a lot of time and effort. An ineffective process occurs when the cleaning staff collects waste in a circular path. Automating garbage collection using a line follower robot with PID control and the blynk application to start and stop as well as a predetermined path at a particular gathering point, can save energy and time for cleaning staff. The tuning value for each PID Control constant P=0.2, I=0.3, and D=0.06 can smooth the robot's movement with the L298N motor driver. It is decided by the Arduino UNO microcontroller and wireless connection using NodeMCU (ESP8266) for direction taking. The reading sent by the infrared sensor with analogRead mode when dimmed is in the range of 175 270, and the maximum reading value of the sensor is 940 950. The decision to turn follows a predetermined line when the sensor is below 175, according to which the sensor hits the line. The robot will stop running when the ultrasonic sensor finds an object or obstacle less than 15 cm in front of it.